Management of Subclinical and Overt Hypothyroidism Following Hemithyroidectomy in Children and Adolescents: A Pilot Study - Chen, Jiarui; Hou, Shule; Li, Xiaoyan; Yang, Jun (Frontiers in Pediatrics, 2019)
Background: To reduce surgical complications and avoid lifelong thyroid hormone replacement, hemithyroidectomy is preferred in children and adolescents with benign nodular thyroid disease. However, hypothyroidism following hemithyroidectomy may occur, and postoperative thyroid hormone replacement for hypothyroidism following hemithyroidectomy is usually administered without a full understanding of the clinical characteristics of hypothyroidism. Methods: To investigate the incidence and risk factors of hypothyroidism after hemithyroidectomy in children and adolescents, and to identify whether postoperative thyroid hormone replacement is necessary, a retrospective review of 43 patients under 18 years of age who underwent hemithyroidectomy from January 2009 to October 2016 was conducted. All hypothyroid patients were retrospectively analyzed to determine the incidence and predisposing factor(s) of postoperative hypothyroidism. All patients were measured regarding age, sex, serum thyrotropin (TSH), anti-thyroid antibody, and histological evidence of lymphocytic infiltration. Hypothyroid patients were measured for symptoms, timing of diagnosis, and thyroid hormone replacement. Results: The mean age at the time of surgery was 13.65 ± 3.04 years. Of the cohort, 34 patients were female (79.07%), and the mean follow-up time was 28 ± 9 months. Hypothyroidism was diagnosed in 11 of the 43 patients. The mean postoperative TSH level was 7.17 ± 2.13 μIU/ml. The mean preoperative TSH level was 3.11 ± 0.59 μIU/ml in hypothyroid patients compared with 1.92 ± 0.72 μIU/ml in euthyroid patients (P < 0.05). A preoperative TSH level >2.2 μIU/l and lymphocytic infiltration graded 3 or 4 were found to be independent risk factors for the development of hypothyroidism. There were no significant differences between groups in terms of patient age or sex. Conclusions: In the pediatric and adolescent population, patients with elevated preoperative TSH levels or the presence of lymphocytic infiltration may increase the risk of risk of hypothyroidism. In our study, postoperative levothyroxine (L-T4) treatment was necessary in 16.28% of cases after hemithyroidectomy. Patients with mild postoperative hypothyroidism should be followed up, without the need for immediate L-T4 replacement, so as to expect patients to recover spontaneously.